Analysis of pricing models for options - Landauskas, Mantas; Valakevičius, Eimutis (Lietuvos matematikos rinkinys, 2009)
The program developed was effective in time of calculation and let us state, that binomial and Markovian models give similar results, but Markovian model is much slower when lattice has more than 25 periods. The crude Monte Carlo Model requires millions of paths to be generated in order to get high accuracy.